CLASSIFICATION OF FACTORS AFFECTING THE DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Sayfullaev Ilkhomjon Abdurahmanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The process of forming a small business in the Republic of Uzbekistan and its regions is of great importance today. Finally, in the conditions of unstable economic relations and crisis economy, in general, small business is one of the means of solving many socio-economic problems. This, in turn, has been confirmed in the context of the Covid-19 pandemic, which has suddenly appeared all over the world. The analysis shows that small business and private entrepreneurship contribute to the weakening of monopolistic tendencies in the national economy by developing intra-industry competition.